공공임대주택에 거주중인 노령인구 인지특성에 관한 연구 - 오예인; 정다운; 권순정 (의료·복지 건축, 2018)
Purpose: Korean society is undergoing the rapid increase and poverty of elderly population. Therefore, the appropriate supply and planning of public rental housing for the low-income elderly is more important. The purpose of this study is to present the basic data for the study and planning of the elderly housing complex by analyzing the cognitive characteristics of the elderly residing in the rental housing. Methods: A questionnaire survey was conducted to identify health characteristics of the elderly living in the 'Gongreung SH Apartment'. 100 random samples were collected and 82 valid samples were analysed. Statistical analysis was performed using Excel and R for the age, sex, health, outdoor walking frequency and characteristics of Cognitive map of the elderly. Results: The characteristics of cognitive map were classified into point shapes and linear shapes. The linear group was lower in average age than the point group and tended to draw the map wider. The wider the map was, the more the number of elements in cognitive map was. The number of elements on the cognitive map decreased as respondents’ age increased. On the other hand it was not related to residence period and gender of the elderly. Implication: The cognitive extent of the residential environment tends to decrease with age. Men's cognitive range is wider than women’s. There is no corelation between the number of cognitive elements and cognitive map type. Men tend to have a systematic image of city, whereas women focus on relational and social urban factors. For sustainable apartment complex design, various characteristics of the group including men and women, different age and different health status should be considered.
Keywords: Cognitive Map; Apartment Complex; Rental Public Apartment; Elderly; Living Environment; 인지도; 아파트단지; 공공임대아파트; 노인; 주거환경